Sustainable approach for building energy optimization based on occupant’s behavior - Nor Azuana, Ramli; Awalin, Lilik J.; Mohd Fairuz, Abdul Hamid (UTeM, 2022)
Modern age has witnessed an increasing dependency of Malaysia’s population towards electricity which was reflected on its distributive high energy consumption. Consequently, a few vital points on energy issues are discussed predominantly in the engineering world on how energy could be utilized optimally. One of the ways of solving this matter is through an Energy Management System (EMS). However, certain issues arise which related to human comfort and real-time parameters as this criterion was set aside in Building Energy Management System (BEMS). Hence, this study was conducted with the aim to improve the system by proposing a more effective methods surrounding the energy efficiency and human comfort factors. Methodologies proposed in this study consists of three parts, which are: (i) correlation analysis of occupant’s behavior with building energy performance, (ii) predictive analysis of energy consumption based on occupant’s behavior, and (iii) sustainable approach through electricity harvesting from radio frequency for powering data-collecting Internet of Things (IoT) devices. Under Microsoft Azure Services, these three methodologies combination were conducted for an aggregate monitoring of building energy consumption and identification of future consumption trend. Other than that, notification services for alteration of occupant’s behavior was constructed as part of energy saving measure.